The threatened Gouldian finch preferentially forages in prescribed burnt savannas - Collett, Sydney J.; Radford, Ian J.; Kaestli, Mirjam; Crewe, Tara L.; Garnett, Stephen T.; Campbell, Hamish A. (International journal of wildland fire, 2023)
Background The granivorous finches of Australia’s tropical savannas heavily rely on a sequence of perennial and annual grass seed production to feed throughout the year. An increase in late dry season wildfires has been suggested to detrimentally effect seed production sequence and has been attributed to poor physiological condition and a reduction in fitness of granivorous finches. Early dry season prescribed burning is an asset protection management strategy often implemented to reduce the incidence of late dry season wildfire, but has also been shown to improve the abundance and nutritional quality of grass seed Aims To assess whether the Gouldian finch (Chloebia gouldiae) preferentially used areas that were subject to early dry season prescribed burning over areas that were not burnt. Methods The creation of a landscape mosaic across the landscape with varying fire histories. Then the assessment of individual finch movement and site utilisation using VHF-radio telemetry transmitters, detected by an array of static receivers deployed across the landscape. Key results Finches significantly preferred to forage in areas burnt in the early season every 2–3 years. Conclusions The study demonstrates that early dry season prescribed burning creates preferred foraging habitat patches for Gouldian finches within savanna fire mosaics.